MAKING PSYCHOGRAPHIC DECISIONS FOR HEALTHY AND SICK PERSONS: QUANTUM GENETIC ALGORITHM, GRAPH NEURAL NETWORKS - Kulishov , Sergii (Collection of scientific papers «ΛΌГOΣ», 2022)
Quantum genetic algoritm, graph neural networks using for making decisions by psychography of healthy and sick persons are present in this publication.